APPLICATION OF ANTHOCYANINS OBTAINED FROM Zea mays L. (PURPLE CORN) AS INHIBITING AGENTS OF AGGREGATION OF AMYLOID AND AMYLOID-TYPE PEPTIDES (AGGREGRATED TRYPSIN) - A. Zaa, César (2021)
β-Amyloid (Aβ) is a toxic peptide that has a high propensity for aggregation, and it is often present in the brains of patients with Alzheimer's disease (AD). Bioactive compounds from medicinal plants with neuroprotective properties are of interest in protecting against toxic forms of the Aβ peptide. In the present work, we evaluate the in vitro antiaggregant / disaggregating capacity of amyloid and amyloid-type aggregates by the anthocyanins of Zea mays L. (purple corn). Using the differential pH method, we quantified the total anthocyanin content. With the help of spectrophotometric readings of the amyloid-like protein-Congo Red and Aβ-Congo Red complexes, we evaluated the antiaggregation and disaggregation effects of anthocyanins on amyloid peptides and amyloid derivatives. The results showed a significant activity of antiaggregant / disaggregating capacity by anthocyanins, (33.54 and 26.63%, respectively) which was dependent on the concentration. In addition, the anthocyanin concentrations found of 32.95 and 280.69 mg / L (in aqueous and acidic methanolic medium, respectively), have been compared with anthocyanins and polyphenols from different sources. The results obtained are encouraging to continue evaluating anthocyanins as potential biological agents.